Design and molecular dynamic simulation of a new double-epitope tolerogenic protein as a potential vaccine for multiple sclerosis disease - Fatemeh Banisharif-Dehkordi; Mohsen Mobini-Dehkordi; Mostafa Shakhsi-Niaei; Karim Mahnam (Wolters Kluwer Medknow Publications, 2019)
One of the debilitating diseases affecting the central nervous system is multiple sclerosis (MS). As there is no definitive treatment for MS, researchers have mainly consented with optimization of strategies which slows down the progression of the disease such as specific auto-antigens tolerance induction. In this regard, the aim of this study was design of a new double-epitope protective vaccine based on interleukin (IL)-16-neuroantigens fusion proteins. First, we selected highly antigenic epitopes of myelin basic protein (MBP) (aa 84-104) and myelin oligodendrocyte glycoprotein (MOG) (aa 99-107) from available literature and our bioinformatics analysis. The correct cleavage of our constructs and major histocompatibility complex class II binding affinities of cleaved epitopes were checked and evaluated using Pepcleave and IEDB servers, respectively. Then, different combination of MOG and MBP epitopes with or without fusion to C-terminal active part of IL-16 were designed as constructs. Afterward, Modeller and Gromacs softwares used for the investigation of the MBP, and MOG epitopes antigenicity in these constructs. The results of molecular dynamics simulations showed that IL-16 in MOG + linker + MBP + IL-16 construct does not interfere with final epitopes antigenicity of MOG + linker + MBP construct. To sum up, the construct with IL-16 is suggested as a new double-epitope tolerogenic vaccine for prevention and amelioration of MS in human.